THE EFFECT OF AUTOGENIC RELAXATION TECHNIQUE ON REDUCINGANXIETY LEVELS IN THIRD-TRIMESTER PREGNANT WOMEN AT TPMBIKE SRI MEI WULAN, BULULAWANG, MALANG REGENCY - Amaliyyah Jazilla; Tut Rayani Aksohini Wijayanti; Anik Purwati (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Primigravida women those experiencing pregnancy for the first time and lacking prior knowledge of physical changes and the childbirth process tend to experience higher levels of anxiety compared to multigravida women. Therefore, non-pharmacological interventions are needed to help facilitate the labor process, one of which is the use of autogenic relaxation techniques to reduce anxiety in third-trimester pregnant women. This study aimed to determine the effect of autogenic relaxation techniques on the anxiety levels of third-trimester pregnant women at TPMB Ike Sri Mei Wulan, Bululawang District, Malang Regency. The research employed a quantitative method with a pre-experimental design using a one-group pretest–posttest approach. The sample consisted of 27 third-trimester pregnant women selected through purposive sampling from a population of 40 individuals. The instrument used was the PRAQ-R2 questionnaire to measure anxiety levels before and after the intervention. Data analysis was conducted using univariate and bivariate methods, with the Wilcoxon Signed Rank Test applied for statistical analysis. The results showed that before the intervention, most respondents experienced moderate anxiety, while after the intervention, the majority experienced mild anxiety. The Wilcoxon test result indicated a p-value of 0.001 (p < 0.05), demonstrating a significant effect of autogenic relaxation techniques in reducing anxiety levels among third-trimester pregnant women. This therapy can be implemented as a non-pharmacological approach to help reduce anxiety in pregnant women during the third trimester.